(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2024)
In this article, based on the theme "A look at the work of the People’s Artist of Uzbekistan, Botir Zakirov, who made a great contribution to the Uzbek national pop art", the works and decisions are being made to perpetuate the memory of Botir Zakirov.